(untitled) (Journal of Tourism and Hospitality Education, 2019)
The paper aims to examine the relationship between social carrying capacity and tourism carrying capacity in the Annapurna Conservation Area (ACA), Nepal (along the popular Annapurna Base Camp Trail). Carrying Capacity is a key indicator in assessing the sustainable tourism development at a given place. The study used Survey Research Design to obtain information from tourist and local residents. From the research, it was evident that the visitors were highly satisfied with the tourism activities, along with conservation and development activities at ACA. Similarly, local residents were satisfied with the development of tourism in ACA, yet they perceived crowding, and congestion, cultural degradation as some impending challenges in the near future. Social Carrying Capacity in the ACA has not exceed its threshold, even though this popular trekking destination has been witnessing robust growth in the number of tourist in the region post armed-conflict (1997-2007). Hypothesis test result indicate that the relationship between dependent variable [Tourism Carrying Capacity (TCC)] and independent variable [Social Carrying Capacity (SCC)] has a positive correlation. Adequate and appropriate management intervention by the Nepal Trust for Nature Conservation (NTNC)/Annapurna Conservation Area Project (ACAP) there has been well-planned and sustained tourism growth in the region.